1999
DOI: 10.1086/520429
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia Caused by Staphylococci with Inducible Vancomycin Heteroresistance

Abstract: The clinical significance of bacteremia due to vancomycin-heteroresistant staphylococci and a rapid laboratory screening method were examined; 203 strains of staphylococci isolated from patients with clinically significant bacteremia were screened by the disk-agar method with use of vancomycin-salt agar to demonstrate satellitism around an aztreonam disk as well as by conventional population screening. Eighteen isolates (three Staphylococcus aureus and 15 coagulase-negative staphylococci) were shown to be hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
128
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(134 citation statements)
references
References 18 publications
4
128
1
1
Order By: Relevance
“…Wong and coworkers [31] also found a similar rate (7.4%) of CNS strains with reduced susceptibility to glycopeptides isolated from bloodstream among 203 patients analyzed. If we considered only bacteremias by CNS the prevalence found in our study would increase for 18.37% (9/49 patients).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Wong and coworkers [31] also found a similar rate (7.4%) of CNS strains with reduced susceptibility to glycopeptides isolated from bloodstream among 203 patients analyzed. If we considered only bacteremias by CNS the prevalence found in our study would increase for 18.37% (9/49 patients).…”
Section: Discussionmentioning
confidence: 64%
“…Thus, our results may also reflect the severity of the patients admitted in this hospital. Wong and coworkers [31] in a case-control study showed that the admission to the intensive care unit, prior use of vancomycin and/or β-lactams and isolation of methicillin-resistant staphylococci were common characteristics among patients with bacteremia due to staphylococci with heteroresistance to vancomycin.…”
Section: Discussionmentioning
confidence: 99%
“…The disk diffusion test and several automated methods of susceptibility testing failed to detect glycopeptide-intermediate, possibly hetero-resistant S. aureus [9]. As vancomycin hetero-resistance appears to be inducible by salt and probably by â-lactam antibiotics [5], a screening method was proposed that looked for satellitism on Mueller-Hinton agar supplemented with vancomycin 4 mg=L and NaCl 4%, around an aztreonam disk, which, in contrast to other â-lactam antibiotics, has no inhibitory effect on gram-positive bacteria [5].…”
Section: Hetero-resistance In Staphylococcus Aureusmentioning
confidence: 99%
“…In contrast, vancomycin (intermediate) resistance is still extremely rare in S. aureus, but hetero-resistance to this drug has already been reported in as many as 9% of 129 MRSA isolates in a survey of seven Japanese university hospitals [3], in a case report from the UK [4], and in three MRSA cases from Hong Kong [5]. Recently, hetero-resistance has also been reported for teicoplanin [6].…”
Section: Hetero-resistance In Staphylococcus Aureusmentioning
confidence: 99%
See 1 more Smart Citation